Antitubercular potential and pH‐driven mode of action of salicylic acid derivatives - Janïs Laudouze; Thomas Francis; Emma Forest; Frédérique Mies; Jean‐Michel Bolla; Céline Crauste; Stéphane Canaan; Vadim Shlyonsky; Pierre Santucci; Jean‐François Cavalier (FEBS Open Bio, 2025)
In the search for new antituberculosis drugs with novel mechanisms of action, we evaluated the antimycobacterial activity of a panel of eight phenolic acids against four pathogenic mycobacterial model species, including Mycobacterium tuberculosis. We demonstrated that salicylic acid (SA), as well as the iodinated derivatives 5‐iodo‐salicylic acid (5ISA) and 3,5‐diiodo‐salicylic acid (3,5diISA), displayed promising antitubercular activities. Remarkably, using a genetically encoded mycobacterial intrabacterial pH reporter, we describe for the first time that SA, 5ISA, 3,5diISA, and the anti‐inflammatory drug aspirin (ASP) act by disrupting the intrabacterial pH homeostasis of M. tuberculosis in a dose‐dependent manner under in vitro conditions mimicking the endolysosomal pH of macrophages. In contrast, the structurally related second‐line anti‐TB drug 4‐aminosalicylic acid (PAS) had no pH‐dependent activity and was strongly antagonized by l‐methionine supplementation, thereby suggesting distinct modes of action. Finally, we propose that SA, ASP, and its two iodinated derivatives could restrict M. tuberculosis growth in a pH‐dependent manner by acidifying the cytosol of the bacilli, therefore making such compounds very attractive for further development of antibacterial agents.